Hubungan Aplikasi Metode EUCS (End User Computing Satisfaction) dengan Kepuasan Kerja Perawat dalam Penggunaan SIMRS di RSUD Dr. Doris Sylvanus Palangka Raya - Deby Kristanto; Meilitha Carolina; Eva Priskila (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Hospitals, as institutions providing healthcare services, must maximize technological advancements. One such advancement is the use of SIMRS (Hospital Management Information System) in accordance with the Indonesian Minister of Health Regulation No. 82 of 2013. The use of SIMRS is predicted to enhance the hospital's efficiency, effectiveness, professionalism, performance, as well as access and services. Nurses' satisfaction in using SIMRS will impact the improvement of patient care quality. One method to evaluate user satisfaction with SIMRS is EUCS (End User Computing Satisfaction), developed by Doll and Torkzadeh, which consists of five dimensions: content, format, accuracy, ease of use, and timeliness. This study aims to determine the relationship between the application of the EUCS method and nurses' job satisfaction in the use of SIMRS at RSUD dr. Doris Sylvanus Palangka Raya. Methods: This research is correlational, employing a cross-sectional design. Respondents were selected using purposive sampling and the chi-square statistical test was used. The sample consisted of 175 inpatient nurses at RSUD dr. Doris Sylvanus Palangka Raya. Results: The chi-square statistical test showed a p-value = 0.000, or a significance level of p < 0.05, indicating that there is a relationship between the application of the EUCS method and nurses' job satisfaction in the use of SIMRS at RSUD dr. Doris Sylvanus Palangka Raya. Conclusion: Effectiveness and efficiency are the primary goals of SIMRS usage, which creates convenience and transparency, ultimately expected to enhance nurses' job satisfaction.